The Federal revenue system: facts and problems, 1961: materials assembled by the committee staff. (Washington, D. C. Government Printing Office, 1959)
This comprises of the materials assembled by the committee staff for the Joint Economic Committee, Congress of the United States
.
At head of title: 86th Congress, 1st session. Joint committee print.
Includes bibliographical footnotes.
oif 01/02/2019
Ref.
Keywords: Taxation; United States